Your fathers, where are they? And the prophets, do they live forever? : a novel - Eggers, Dave (Alfred A. Knopf/McSweeney's Books, 2014)
In a barracks on an abandoned military base, miles from the nearest road, Thomas watches as the man he has brought wakes up. Kev, a NASA astronaut, doesn't recognize his captor, though Thomas remembers him. Kev cries for help. He pulls at his chain. But the ocean is close by, and nobody can hear him over the waves and wind. Thomas apologizes. He didn't want to have to resort to this. But they really needed to have a conversation, and Kev didn't answer his messages. And now, if Kev can just stop yelling, Thomas has a few questions.